Systematic evaluation of the methodology of randomized controlled trials of anticoagulation in patients with cancer - Rada, Gabriel (BioMed Central, 2013)
BACKGROUND: Randomized controlled trials (RCTs) that are inappropriately designed or executed may provide biased findings and mislead clinical practice. In view of recent interest in the treatment and prevention of thrombotic complications in cancer patients we evaluated the characteristics, risk of bias and their time trends in RCTs of anticoagulation in patients with cancer. METHODS: We conducted a comprehensive search, including a search of four electronic databases (MEDLINE, EMBASE, ISI the Web of Science, and CENTRAL) up to February 2010. We included RCTs in which the intervention and/or comparison consisted of: vitamin K antagonists, unfractionated heparin (UFH), low molecular weight heparin (LMWH), direct thrombin inhibitors or fondaparinux. We performed descriptive analyses and assessed the association between the variables of interest and the year of publication. RESULTS: We included 67 RCTs with 24,071 participants. In twenty one trials (31%) DVT diagnosis was triggered by clinical suspicion; the remaining trials either screened for DVT or were unclear about their approach. 41 (61%), 22 (33%), and 11 (16%) trials respectively reported on major bleeding, minor bleeding, and thrombocytopenia. The percentages of trials satisfying risk of bias criteria were: adequate sequence generation (85%), adequate allocation concealment (61%), participants’ blinding (39%), data collectors’ blinding (44%), providers’ blinding (41%), outcome assessors’ blinding (75%), data analysts’ blinding (15%), intention to treat analysis (57%), no selective outcome reporting (12%), no stopping early for benefit (97%). The mean follow-up rate was 96%. Adequate allocation concealment and the reporting of intention to treat analysis were the only two quality criteria that improved over time. CONCLUSIONS: Many RCTs of anticoagulation in patients with cancer appear to use insufficiently rigorous outcome assessment methods and to have deficiencies in key methodological features. It is not clear whether this reflects a problem in the design, conduct or the reporting of these trials, or both. Future trials should avoid the shortcomings described in this article.